The Establishment of Forest Plantation - Widowati, Arti; Haneda, Noor Farikhah (Jurnal Manajemen Hutan Tropika, 1999)
The establishment of forest plantation of Eucalyptus deglupta in the humid tropic, for pulp and paper industry has so far been hindered seriously by insect stem borer larvae (Zeuzera coffeae ), damaging young and mature stands, and cause important financial lost. Coupling with integral forest pest management and good silvicultural treatements, a strategy for resistance breeding program to stem borer larvea need to be developped for that promising species, in order to establish sound industrial plantation and to accelerate genetic gain achievement per unit time. This study deal with the assement of E. deglupta woods properties, (including anatomical, physicals properties, and chemical substances), that may supposedly be directly implied in resistency mechanisms of Leda againts insect stem borer attack. The preliminary results indicated that sound, tolerant and resistant indvidual trees tend to have higher wood density, than unhealty one. Sound, resistant and tolerant trees tend also to have greater and statistically different in fiber length, fiber diameter, cells walls thickness and lumen diameter than that of unhealty one, especially from that one that have been fortly attacked by stem borer. The preliminary results also indicated that resistance trees tend to exhibit more alcaloid, terpenoid and flavonoid content than the unhealty one. However, the results need to be confirmed by addition of more wood samples to be analyzed for each type of degree of insect injury.